Dosimetry of Skin-Contact Exposure to Tritium Gas Contaminated Surfaces - Legare, Michele (My University, 1991)
The radiological hazards from tritium are usually associated with exposure to tritium oxide either by inhalation, ingestion or permeation through skin. However, exposure from skin-contact with tritium gas contaminated surfaces represents a different radiological hazard in tritium removal facilities and future fusion power plants. Previous experiments on humans by Eakins et al. (8), and more recent experiments on hairless rats at Chalk River Laboratories have shown that when a tritium gas-contaminated surface is brought into contact with intact skin, high concentrations of organically-bound tritium in urine and skin are observed which were not seen from single tritiated water (liquid or vapour form) contamination. The results of the rat experiments, which involved measurements of tritium activity in urine and skin, after contact with contaminated stainless steel, are described. These results are also compared to previous data from human experiments. The effect of various exposure conditions and different contaminated surfaces such as brass, aluminum and glass are analysed and related to the results from contaminated stainless steel exposure. Dosimetric models are being developed in order to improve the basis for dose assessment for this mode of tritium uptake. The presently studied model is explained along with the assumptions and methods involved in its derivation. The features of 'STELLA', the software program used to implement the model, are discussed. The methods used to estimate skin and whole body dose from a model are demonstrated. Finally, some experiments for improving the accuracy of the model are proposed. Briefly, this study compares the results from animal and human experiments as well as different exposure conditions, and determine the range of whole body and skin dose that may be involved from skin-contact intake. This information is essential for regulatory purposes particularly in the derivation of doses for skin-contact contamination.
Tritium Skin-Contact Dosimetry
Keywords: dosimetry; skin-contact exposure; tritium gas